Standing is associated with insulin sensitivity in adults with metabolic syndrome - Garthwaite Taru; Sjöros Tanja; Koivumäki Mikko; Laine Saara; Vähä-Ypyä Henri; Saarenhovi Maria; Kallio Petri; Löyttyniemi Eliisa; Sievänen Harri; Houttu Noora; Laitinen Kirsi; Kalliokoski Kari; et al. (Australia, 2022)
Abstract
Objectives
To determine how components of accelerometer-measured sedentary behavior (SB) and physical activity (PA), and fitness are associated with insulin sensitivity in adults with metabolic syndrome.
Design
Cross-sectional.
Methods
Target population was middle-aged (40–65 years) sedentary adults with metabolic syndrome. SB, breaks in SB, standing, and PA were measured for four weeks with hip-worn accelerometers. VO2max (ml/min/kg) was measured with maximal cycle ergometry. Insulin sensitivity was determined by hyperinsulinaemic-euglycaemic clamp (M-value) and fasting blood sampling (HOMA-IR, insulin). Multivariable regression was used for analyses.
Results
Sixty-four participants (37 women; 58.3 [SD 6.8] years) were included. Participants spent 10.0 (1.0) h sedentary, 1.8 (0.6) h standing, and 2.7 (0.6) h in PA and took 5149 (1825) steps and 29 (8) breaks daily. In sex-, age- and accelerometer wear time-adjusted model SB, standing, steps and VO2max were associated with M-value (β = −0.384; β = 0.400; β = 0.350; β = 0.609, respectively), HOMA-IR (β = 0.420; β = −0.548; β = −0.252; β = −0.449), and insulin (β = 0.433; β = −0.541; β = −0.252; β = −0.453); all p-values < 0.05. Breaks associated only with M-value (β = 0.277). When further adjusted for body fat %, only standing remained significantly associated with HOMA-IR (β = −0.381) and insulin (β = −0.366); significance was maintained even when further adjusted for SB, PA and fitness. Light and moderate-to-vigorous PA were not associated with insulin sensitivity.
Conclusions
Standing is associated with insulin sensitivity markers. The association with HOMA-IR and insulin is independent of adiposity, PA, SB and fitness. Further studies are warranted, but these findings encourage replacing sitting with standing for potential improvements in insulin sensitivity in adults at increased type 2 diabetes risk.
Abbreviations
APEangle for posture estimation; BPblood pressure; FFMfat free mass; HOMA-IRhomeostatic model assessment of insulin resistance; LPAlight physical activity; MADmean amplitude deviation; METmetabolic equivalent; MetSmetabolic syndrome; MVPAmoderate-to-vigorous physical activity; NEFAnon-esterified fatty acids; PAphysical activity; SBsedentary behavior; T2Dtype 2 diabetes; WCwaist circumference